PENCIPTAAN BUKU ILUSTRASI TAMAN SARI KERATON YOGYAKARTA SEBAGAI UPAYA PENGENALAN CAGAR BUDAYA - Ridhani, Nur Dyanto Riski; Fianto, Achmad Yanu Alif; Yosep, Sigit Prayitno (Jurnal Art Nouveau, 2015)
Abstract: Taman Sari Keraton Yogyakarta is one of the curtural heritage in Indonesia who have cultural values and symbols of royal power that reigned at the time. Is currently only used as a cultural heritage of society as a place traveled without preserving the building. During this time many media lift Taman Sari as beautiful objects that need to be visited without explaining in detail one by one part of Taman Sari that historical element in Taman Sari is not known by the public. For the book illustration is made by way of explaining in detail the functions parts of Taman Sari on Sri Sultan HamengkuBuwono 1 and as a result of the reconstruction of buildings have been destroyed that can not be done with photography and videography. Creation of book illustration is done by using qualitative research methods, the approach of observation, interviews and literature studies. The Picture of Peaceful concept implemented using illustrations with wet dye technique or watercolor. The Picture of Peaceful concept derived from observation, interviews reinforced with the theoretical basis of several studies literature resulting illustration book Taman Sari Keraton Yogyakarta which describes the overall usability of the Taman Sari during functionalized.Â Keywords: Illustrated Book, Taman Sari, Yogyakarta